The Kiruna seismic event: important insights from the geotechnical model - Mawson, M; Dahnér-Lindkvist, CR; Andersson, UB; Thomas, A; Bäckström, A (Caving 2022: Fifth International Conference on Block and Sublevel Caving, 2022)
Luossavaara-Kiirunavaara Aktiebolag’s Kiirunavaara Mine is an iron ore mine located in Sweden’s Lapland. On 18 May 2020, a seismic event of moment magnitude (Mw) 4.2, calculated on the Swedish National Seismic Network (SNSN) and international systems, caused extensive damage to tunnel infrastructure and halted production in Block 22. A study was conducted to investigate the causes and evaluate how to safely restart mining. As discussed in this paper, the study included detailed reviews of existing datasets of core logging, drift mapping, and damage mapping following the event. In addition, new data was collected from drillholes targeting the interpreted area of the seismic source. Geotechnical data interrogation, structural modelling, and rock mass characterisation served to characterise the seismic source area in greater detail, leading to a full description of the crush zone: a zone of weaker rock mass which obliquely cuts the orebody – interpreted as an early extensional fault breccia of probable hydrothermal origin. The crush zone is identified to be susceptible to damage resulting from the seismic event. Associated with the crush zone, strong porphyry intrusions have resulted in complex lithological–structural relationships. This paper highlights the investigation into the source area of the seismic event and demonstrates how geotechnical data integration can give important insights to major mine planning decisions.
Keywords: seismic event; geotechnics; modelling